Implementing Samba 4 : exploit the real power of Samba 4 Server by leveraging the benefits of an Active Directory Domain Controller - Leal, Marcelo (Community experience distilled., 2014)
This book is an implementation tutorial covering step-by-step procedures, examples, and sample code, and has a practical approach to set up a Samba 4 Server as an Active Directory Domain Controller and also set up different Samba 4 server roles. This book is ideal for system administrators who are new to the Samba 4 software, and who are looking to get a good grounding in how to use Samba 4 to implement Active Directory Services. It's assumed that you will have some experience with general system administration, Active Directory, and GNU/Linux systems. Readers are expected to have some test mac.